2012
DOI: 10.1177/0954406212459698
|View full text |Cite
|
Sign up to set email alerts
|

Precision motion control of permanent magnet linear synchronous motor servo system based on an integrated controller with inertia variation compensation

Abstract: To achieve high robustness and precise motion control of permanent magnet linear synchronous motor servo system, an integrated controller is presented, including a velocity feed forward controller, a zero phase error tracking controller, a disturbance observer and inertia variation compensator. The velocity feed forward controller and the zero phase error tracking controller are included to improve tracking performance and the disturbance observer is involved to enhance disturbance rejection. However, both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…If the inertia is properly identified, appropriate actions can be taken with further compensation. The inertia was identified by a model reference adaptive method in Li et al (2013) and the feedforward compensation gain was tuned accordingly. An adaptive controller was proposed in Li and Liu (2009) for speed regulation servo systems by combining extended state observer with inertia identification method.…”
Section: Introductionmentioning
confidence: 99%
“…If the inertia is properly identified, appropriate actions can be taken with further compensation. The inertia was identified by a model reference adaptive method in Li et al (2013) and the feedforward compensation gain was tuned accordingly. An adaptive controller was proposed in Li and Liu (2009) for speed regulation servo systems by combining extended state observer with inertia identification method.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, inertia identification is a straightforward technique to compensate for inertia variations. A model reference adaptive method was adopted in [1] for inertia identification and the feedforward compensation gain was tuned accordingly. The work in [2] combined the extended state observer with the inertia identification method and proposed an adaptive controller for speed regulation servo systems.…”
Section: Introductionmentioning
confidence: 99%
“…If the inertia can be properly identified, appropriate actions can be taken with further compensation. In Li et al, 5 the inertia was identified by a model reference adaptive method, and the feedforward compensation gain for inertia variations was tuned according to inertia identification. Jee and Lee 6 and Jin et al 7 presented several kinds of inertia identification algorithms and tuning schemes of control parameters.…”
Section: Introductionmentioning
confidence: 99%